The Role of Stereotactic Radiosurgery in the Treatment of Large Brain Metastases - O. L. Evdokimova; A. S. Tokarev; V. A. Rak; A. A. Grin; A. V. Prirodov (Неотложная медицинская помощь, 2022)
Stereotactic radiosurgery is a modern treatment modality for patients with intracranial metastases. However, it has long been acknowledged that radiosurgery of large tumors results in limited efficacy and increased rate of complications. There have been still debates on the need of combination of radiosurgery and open surgery for intracranial metastases and the sequence of these modalities. The next question is about the proper treatment for metastases that could not be resected. There is a paucity of data describing the relationship between radiosurgical options and radiobiological effect, in particular how prescribed dose, type of fractionation, volume of irradiated tumor and morphology of cancer are related. The information presented in this review highlights opportunities of stereotactic radiosurgery for treatment of patients with large intracranial metastases in combination with open surgery as well as a stand-alone method when using hypofractionation regimen.